Human Papillomavirus and Head and Neck Cancer - Walline, Heather (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the study of head and neck squamous cell carcinoma (HNSCC), we know that virally induced malignancies behave differently than those generated through other carcinogenic mechanisms. This paradigm extends into differences in tumor growth, treatment response and resistance, as well as invasion and metastasis. The inability to correctly diagnose and appropriately treat HNSCC at early stages has contributed to reduced survival for HNSCC patients, particularly those with HPV-negative disease. The examination of the molecular differences between HPV-positive and HPV-negative HNSCC will provide support for early diagnostic markers and guide appropriate treatment selection to improve patient care and survival.This Special Issue highlights current research efforts to understand the evolving contribution of human papillomavirus in HNSCC.